Evidence of Urtica dioica Agglutininʼs Antiproliferative and Anti-migratory Potentials on the Hyaluronic Acid-Overexpressing Prostate Cancer Cells - Heydari, Mohammadkazem; Hosseinzadeh Colagar, Abasalt; Sabour, Davood; Khorasani, Hamid Reza (Planta Medica, 2024)
Hyaluronic acid is composed of repeating sugar units, glucuronic acid and N-acetylglucosamine, which are often associated with increased tumor progression. Urtica dioica agglutinin is a potential component that exhibits a high affinity for binding to N-acetylglucosamine. This study aimed to investigate U. dioica Agglutininʼs potential to inhibit the proliferation and migration of prostate cancer cells with high expression of hyaluronic acid through molecular docking and in vitro studies. The expression of hyaluronan synthase genes in prostate tissue and cell lines was checked by an in silico study, and the interaction between hyaluronic acid with both CD44 transmembrane glycoprotein and U. dioica agglutinin was analyzed through molecular docking. U. dioica Agglutininʼs effect on cell viability (neutral red uptake assay), migration (scratch wound healing assays), and both CD44 and Nanog expression (quantitative real-time polymerase chain reaction) were assessed in vitro. The results showed that in prostate cancer cell lines, the PC3 cell line has the highest expression of hyaluronan synthase genes. U. dioica agglutinin exhibits an interaction of six specific residues on CD44 compared to hyaluronic acidʼs singular residue. While U. dioica agglutinin alone effectively reduced cell viability and wound closer (≥ 150 µg/mL), combining it with hyaluronic acid significantly shifted the effective concentration to a higher dose (≥ 350 µg/mL). These results, together with low Nanog and high CD44 gene expression, suggest that U. dioica agglutinin may impair the CD44-HA pathway in PC3 cells. This possibility is supported by U. dioica Agglutininʼs ability to compete with hyaluronic acid for binding to CD44. Based on this, U. dioica agglutinin as a plant lectin shows promise in inhibiting cancer proliferation and migration by targeting its dependence on hyaluronic acid.
Keywords: CD44 receptor; cell proliferation; hyaluronic acid; prostate cancer; Urtica dioica agglutinin